Optimization of in house lysis reagent concentration towards the performance of sus scrofa DNA detection system / Nur Arina Ahmad Spain - Ahmad Spain, Nur Arina (2007)
The purpose of this study were to design an optimized DNA extraction method which can produce optimum DNA yield and purity and to link the optimized DNA extraction method and PCR reaction in order to develop a porcine DNA detection system that can be commercialized for halal liaratn authentication of pharma-cosmeceutical products. There are two testing parameters used in this study and comparison between these two testing parameters and standard parameter of in house DNA extraction method was made in te1111s of efficiency to extract genomic DNA. This study was begun with in house DNA extraction using the all parameters as well the standard, followed by running nucleic acid gel electrophoresis to determine the size of the extracted genomic DNA. Next, the efficiency of all parameters used was confirmed with PCR assays. PCR assays will amplify the target DNA sequence, therefore its sensitivity and specificity is very important. At the final step, nucleic acid gel electrophoresis was nm to determine to size of the PCR products as well as to verify the efficiency of the two parameters. In conclusion, the two testing parameters used in this study have same efficiency as the standard parameter, and therefore can be used to replace the standard parameter. The results show that all pharma-cosmeceutical samples tested are free from porcine DNA. The efficiency of the optimized in house DNA extraction method is proven by the successive PCR assay.